Kajian Literatur Konsep Islam Tentang Hak Asasi Manusia dan Demokrasi di Indonesia - Untoro, Joko; Ridwan, Muannif; Indrawan, Irjus (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2025)
Human rights and democracy are important topics in society and the state. Democracy is a system of government that involves the active participation of the people which is closely related to human rights, which includes equality of rights and obligations. This research focuses on the Islamic concept of human rights and democracy in Indonesia. This research uses descriptive qualitative research methods. The type of research is normative research or commonly referred to as library research, which is collecting data or papers related to human rights and democracy in Indonesia in terms of Islamic law. The results of this study state that Islam has a firm and deep understanding of human rights and democracy derived from the teachings of the Qur'an and Sunnah. Islam affirms that every human being has fundamental rights that must be respected, such as the right to life, liberty, justice, and equal treatment. Democracy, on the other hand, provides freedom to the people while taking into account the rights of each individual. In Islam, the main principles related to this include: 1) The principle of justice ('adl); 2) The principle of rights (haqq); 3) The principle of freedom (hurriyah). The concepts of human rights and democracy in Islam encompass both worldly dimensions and transcendental values that emphasize human responsibility to God and others. This approach makes Islam a guideline